Identification of volatile compounds in lactating bovine (Bos taurus) urine - KUMAR, K RAMESH; RAJANARAYANAN, S; ARCHUNAN, G (The Indian Journal of Animal Sciences, 2014)
Urinary chemical profiles of lactating cows at three different periods (early, mid and late lactation) studied for the presence of volatile compounds using gas chromatography-mass spectrometry (GC-MS). revealed nearly II compounds (alkanes, alkenes, alcohol, ketone etc.) and that the studied chemical profiles of the lactating urine do nor correlate with the compounds present in ovulatory urine. Among rhe identified compounds 2, 2-dimethylbutane is found invariably in all the three periods. cyanoacetic acid. found in early and late phases but absent in mid phase, I-iodotetradecane. is absent in early phase but present in mid and late phases. Furthermore, the results suggested that the presence of specific compounds in lactating urine during lactation in a particular phase or time may act as chemical signals for the maintenance of reproduction/social communication.